Environmental assessment of bio‐based chemicals in early‐stage development: a review of methods and indicators. (9th May 2017) - Broeren, Martijn L.M.; Zijp, Michiel C.; Waaijers‐van der Loop, Susanne L.; Heugens, Evelyn H.W.; Posthuma, Leo; Worrell, Ernst; Shen, Li
Abstract: Climate change and fossil resource depletion are driving a transition to a bio‐based economy, for which novel bio‐based chemical processes need to be developed. The environmental performance of the novel bio‐based chemicals should be assessed during their development, when the production process can still be adapted, although data availability is limited. Many environmental assessment methods applicable during product development ('early‐stage methods') exist in the literature. The aim of this study is to provide an overview of these early‐stage methods and to evaluate to what extent they are suitable for assessing bio‐based chemicals in their early‐stage development. The paper first describes the characteristics of early‐stage chemical design and the environmental impacts of bio‐based products based on published life cycle assessments. Low data requirements, the inclusion of climate change and energy indicators, and the inclusion of environmental impacts from biomass feedstock production are identified as three good‐practice principles for early‐stage assessment of bio‐based chemicals. In the second step, 27 early‐stage assessment methods are reviewed and categorized based on their scope and environmental indicators used. Finally, the reviewed methods are evaluated using the good‐practice principles. A perfect early‐stage method does not exist. However, choosing the most suitable method(s) based on the goal of an assessment and using complementary indicators leads to the most effective assessment for novel bio‐based chemicals in development. © 2017 The Authors. Biofuels, Bioproducts and Biorefining published by Society of Chemical Industry and John Wiley & Sons, Ltd.